Pregnancy-acquired memory CD4+ regulatory T cells improve pregnancy outcome in mice - Kristin Thiele; Christopher Urbschat; Julia. Isabel. Amambay Riquelme; Lisa. Sophie Ahrendt; Ronja Wöhrle; Steven Schepanski; Judith Joana Eckert; Etienne Becht; Minyue Qi; Malik Alawi; Martin Becker; Nicola Gagliani; et al. (Nature Communications)
Abstract Subsequent pregnancies are generally less prone to obstetric complications. A successful pregnancy outcome requires pivotal immunological adaptation to ensure immune tolerance towards the foetus. Thus, the lower risk for pregnancy complication during subsequent pregnancies may be attributable to immune memory mounted during first pregnancies. Here we identify higher frequencies of fetal-antigen-specific CD4+ regulatory T (Treg) cells both postpartum and in subsequent pregnancies in mice which are partly originating from trans-differentiated Th17 cells. Our functional experiments demonstrate that these CD4+ Treg cells have memory functions (CD4+ mTreg) and account for an improved fetal development and pregnancy outcome, also during adverse conditions, such as gestational sound stress. Using a high-throughput single-cell quantification method, we identify candidate markers for the detection of CD4+ mTreg cells, which include CXCR4 and CD274. Our findings thus contribute to the improved understanding of pregnancy-induced immune memory and foster the identification of immune targets aiming to reduce the risk for immune-mediated pregnancy complications.